2021
DOI: 10.3390/brainsci11070934
|View full text |Cite
|
Sign up to set email alerts
|

Can Incobotulinumtoxin-A Treatment Improve Quality of Life Better Than Conventional Therapy in Spastic Muscle Post-Stroke Patients? Results from a Pilot Study from a Single Center

Abstract: Post-stroke spasticity frequently occurs in patients with stroke, and there is a need for more quality-of-life assessments for different therapies. We evaluated for the first time in Romania the quality of life among patients with post-stroke spasticity, comparing two therapies over a 6-month period: botulinum toxin type A (BOT) with conventional therapy (CON). We also assessed the reduction of spasticity and functionality secondary to the increase in the mobility in upper limbs. This study was based on a pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The quality of life of stroke patients is also affected by the presence of spasticity. Botulinum toxin therapy has a favorable impact on the evolution of and increase in the quality of life of these patients by reducing spasticity [45]. Thus, if we are to talk only about the quality of the patient's life, we must also take into account the fact that 60% of these patients also have a cognitive impairment [46].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of life of stroke patients is also affected by the presence of spasticity. Botulinum toxin therapy has a favorable impact on the evolution of and increase in the quality of life of these patients by reducing spasticity [45]. Thus, if we are to talk only about the quality of the patient's life, we must also take into account the fact that 60% of these patients also have a cognitive impairment [46].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the treatment with botulinum toxin in these patients is not only to improve their functionality, in many cases, the goal is to improve joint ranges of motion and muscle extensibility to facilitate care, hygiene and even improve limb posture. Moreover, it has been suggested that incobotulinumtoxinA increased quality of life by improving movement, daily activities, mental health, and muscle tone more effectively than conventional therapy 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of post-stroke QoL demands an integrated view of each patient. Management of specific social or health problems, for instance, spasticity, can have a large impact in multiple domains of QoL [23].…”
Section: Discussionmentioning
confidence: 99%